The Meaning of Gojek Advertising in the Pandemic Era Using Charless Sander Pierce Semiotics Analysis - Afny Rachma Safitri; Alvina Tara Afifa; Achmad Chusaini Nasichul Amin; Adi, Nur Romdlon Maslahul (Da’wa and Communication Faculty of the Sunan Ampel State Islamic University, Surabaya, Indonesia., 2021)
The business competition faced by companies today is getting tighter, so it requires company management to be attentive in determining its competitive strategy. Advertising is tot only to promote a product, but also included a lot of social messages in it. Advertisements often use symbols or signs in describing their products. The messages in advertisements are in the form of text and visuals. This study aims to analyze the Sign, Object, Interpretant as well as the message and meaning in the Gojek advertisement version of “Pesan dari Rumah Buat Kita yang di Jalan”. The research method uses a descriptive qualitative approach; this study uses the semiotic analysis method of the Charles Sander Pierce model. The results of the study show that the Gojek advertisement version of